Seasonal occurrence of foliar fungal and bacterial diseases of mulberry in South India - and R.K. DATTA, V. GUNASEKHAR, TOMY PHILIP, GOVINDAIAH D.D. SHARMA, B. NAGARAJ* (Indian Phytopathology, 2002)
A survey on the incidence and severity of foliar fungal and bacterial diseases of mulberry was conducted during 1990-92 in selected mulberry growing areas under different agroclimatic zones located in Andhra Pradesh, Karnataka, Kerala and Tamil Nadu. Disease incidence was recorded twice in each season at a regular interval of two months on leaf spot, leaf rust, powdery mildew, leaf blight and bacterial blight diseases. The survey was conducted in 5-10 farmers gardens in different villages at Anantapur, Mysore, Madivala, Sirsi, Chamarajanagar, Kanjirapalli, Palghat, Coimbatore and Coonoor. Incidence and severity of diseases were more during rainy season followed by winter and summer. All the diseases were indexed in most of the places of survey during rainy and winter seasons. However, leaf rust and bacterial blight were not recorded at Coonoor in any of the survey periods. The incidence and severity of various diseases in different seasons are discussed.